Interlinking financial stability regulation and governance in German professional soccer: contribution and implications - Adam, Sandy; Bachmaier, Birgit (Frontiers in Sports and Active Living, 2024)
This study explores the integration of financial stability regulation in professional soccer within the framework of sport governance, focusing on the German context. The research examines how financial regulations influence key governance principles such as accountability, transparency, and sustainability, while also addressing the challenges posed by the dynamic nature of professional soccer.Methods: A qualitative methodology was employed, using focus group discussions with nine experts, including representatives from soccer clubs, auditing firms and other relevant stakeholders. The discussions aimed to capture diverse perspectives on the impact of financial stability regulation on governance practices within the German soccer league and clubs.The findings reveal that financial stability regulation is effective in promoting financial discipline and accountability at both league and club levels. However, the study also identifies challenges, such as the need for greater harmonization of regulatory frameworks across different levels of professional soccer and the potential benefits of implementing incentive mechanisms within the financial stability regulation to improve governance at the league and club levels.The study underscores the importance of a multi-dimensional approach to financial stability regulation, considering political, systemic, and organizational dimensions. It highlights the potential for improving governance through the adoption of independent governance models and more practical applications of governance principles. Future research could further explore these areas, offering insights that could enhance the effectiveness of financial regulation in professional soccer and potentially other sport contexts.